ANALISIS SISTEM PENGUASAAN LAHAN PETANI PEPAYA DAN PISANG DI KAMPUNG KOYA KOSO DISTRIK MUARA TAMI KOTA JAYAPURA - Demas Wamaer (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2008)
The research aims are to know the land use and own system for agriculture in Koya Koso Village. It can give the information to Jayapura City government and local people. This research was using descriptive analysis method for 30 banana and papaya farmers as respondents from three categories (non owner non local people; owner local people; non owner local people) with 10 farmers each. Result of research was showed that though farmers (category 1 and 3 ) were never having a formal the land use and own system, the on farm bananas and papaya was benefit to non owner (R/C 3,77 and 3,36). The analysis of farmer income were showed that in spite of this will pay for tax and rent of land. it is giving the benefit to farmers non owner the land (R/C: 3,18 and 2,83).